Digital technologies as a logistics and supply chain management tool in economy - S. A. UvarovМ. N. Grigoryev, O. D. Polezhaeva, (Opción, 2019)
The study aims to investigate digital technologies as a logistics and supply chain management tool in the 21st-century economy via comparative qualitative research methods. As a result, the implementation of state-of-the-art digital technologies and the establishment of digital platforms in the member states of the Eurasian Economic Union will result in the realization of the competitive advantages. In conclusion, the digital economy fosters the establishment of information space, taking into consideration the needs of individuals and society in high-quality and reliable information.